Depot-specific adaption of adipose tissue for different exercise approaches in high-fat diet/streptozocin-induced diabetic mice - Guo, Yifan; Zhang, Qilong; Zheng, Lifang; Shou, Jian; Zhuang, Shuzhao; Xiao, Weihua; Chen, Peijie (Frontiers in Physiology, 2023)
Background: Adipose tissue pathology plays a crucial role in the pathogenesis of type 2 diabetes mellitus. Understanding the impact of exercise training on adipose tissue adaptation is of paramount importance in enhancing metabolic health. In this study, we aimed to investigate the effects of various exercise modalities on three distinct adipose tissue depots, namely, interscapular brown adipose tissue (iBAT), subcutaneous white adipose tissue (sWAT), and epididymal white adipose tissue (eWAT), in a murine model of diabetes. Methods: Male C57BL/6J mice received a 12-week high-fat diet and a single injection of streptozotocin, followed by an 8-week exercise intervention. The exercise intervention included swimming, resistance training, aerobic exercise, and high-intensity interval training (HIIT). Results: We found that exercise training reduced body weight and body fat percentage, diminished adipocyte size and increased the expression of mitochondria-related genes (PGC1, COX4, and COX8B) in three adipose tissue depots. The effects of exercise on inflammatory status include a reduction in crown-like structures and the expression of inflammatory factors, mainly in eWAT. Besides, exercise only induces the browning of sWAT, which may be related to the expression of the sympathetic marker tyrosine hydroxylase. Among the four forms of exercise, HIIT was the most effective in reducing body fat percentage, increasing muscle mass and reducing eWAT adipocyte size. The expression of oxidative phosphorylation and thermogenesis-related genes in sWAT and eWAT was highest in the HIIT group. Conclusion: When targeting adipose tissue to improve diabetes, HIIT may offer superior benefits and thus represents a more advantageous choice.